“Foi um acalento para o coração": reflexões de terapeutas ocupacionais atuantes em enfermarias pediátricas a partir da vivência em uma comunidade virtual de prática - Souza, Lucas Ramon Santos de (Universidade Federal de São Carlos, 2025)
The pediatric ward has been a field of practice where occupational therapists have developed their interventions, enabling them to cope with the process of illness and hospitalization. However, studies are needed to improve these practices. In this sense, communities of practice have been consolidated as an effective form of professional training, by promoting the quality of daily practices. The main objective of this study was to investigate aspects of the practice of occupational therapists in pediatric wards, based on emerging themes in a virtual community of practice. Specifically, to identify contributions and challenges of this work and to understand the strengths and weaknesses of a virtual community of practice. This is a descriptive action research with a qualitative approach. The research was conducted through a virtual community of practice, in 11 synchronous remote meetings via Google Meet®, held biweekly, lasting one to one and a half hours, between April and August 2023. The topics of the meetings were chosen in advance by the occupational therapists and included scientific materials to promote reflections. After each meeting, a chronicle was prepared, validated by the participants, containing a summary of the main events. The transcripts of the meetings were analyzed by Content Analysis, with the aid of the qualitative analysis software, ATLAS.ti®. The virtual community of practice had the participation of five occupational therapists, recently graduated and experienced, who provide care in pediatric wards in different locations in Brazil; two occupational therapists who were researchers and organizers; and two Occupational Therapy students as collaborators. Data analysis resulted in three thematic categories: “Constructions of being an occupational therapist to work in a pediatric ward”, which identifies, based on the participants’ conceptions, the skills needed to work in a pediatric ward and the investments in training for this role. “Performance of the occupational therapist in a pediatric ward”, presents the routine of work in this environment, highlighting the intervention process, evidencing the aspects evaluated and the lack of use of standardized assessment instruments. Also noteworthy is the reasoning for the elaboration of therapeutic objectives and the difficulties in communicating about the practice of occupational therapy with other health professionals and family members. The results highlight the difficulties faced by occupational therapists, regarding limited resources, work overload, lack of knowledge of their work by other health professional categories and the consequences of a medically centered environment. As specificities of the occupational therapist’s work, the use of play, the impacts on daily life and the analysis of occupations during hospitalization were listed. “Operationalizing a virtual community of practice” highlights the tools and strategies adopted, as well as the challenges for its structuring, highlighting its benefits, considering it as a space for professional improvement, which guides practices, the formation of a collaborative network, the reduction of the feeling of isolation and the integration between professionals in the field and academia. Concluded that the study can contribute with guidelines to qualify and support the care practice of occupational therapists in pediatric wards.
“It was a warmth for the heart”: reflections of occupational therapists working in pediatric wards based on their experience in a virtual community of practice
Keywords: Terapia ocupacional; Comunidade de prática; Criança hospitalizada; Adolescente hospitalizado; Familiares acompanhantes; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL